2013
DOI: 10.1371/journal.pone.0053450
|View full text |Cite
|
Sign up to set email alerts
|

Ehrlichiosis, Babesiosis, Anaplasmosis and Hepatozoonosis in Dogs from St. Kitts, West Indies

Abstract: BackgroundAlthough tick-borne diseases are important causes of morbidity and mortality in dogs in tropical areas, there is little information on the agents causing these infections in the Caribbean.MethodologyWe used PCRs to test blood from a cross-section of dogs on St Kitts for Ehrlichia (E.) canis, Babesia (B.) spp., Anaplasma (A.) spp. and Hepatozoon (H.) spp. Antibodies against E. canis and A. phagocytophilum/platys were detected using commercial immunochromatography tests. Records of the dogs were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 51 publications
(104 reference statements)
5
61
1
1
Order By: Relevance
“…In the Caribbean region, Kelly et al (2013) were not molecularly detected in dogs in the present study, these agents have previously been detected in dogs in Brazil. For instance, A. phagocytophilum has been detected in dogs and ticks, namely in R. sanguineus and A. cajennense, in the state of Rio de Janeiro .…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In the Caribbean region, Kelly et al (2013) were not molecularly detected in dogs in the present study, these agents have previously been detected in dogs in Brazil. For instance, A. phagocytophilum has been detected in dogs and ticks, namely in R. sanguineus and A. cajennense, in the state of Rio de Janeiro .…”
Section: Discussioncontrasting
confidence: 57%
“…Dogs parasitized by multiple pathogen-infected ticks may have an unknown clinical outcome that depends on the host-parasite relationship. Studies on interactions between tick-borne agents and Leishmania parasites with regard to establishment and progression of the disease are much needed (SOUSA et al, 2013 (CARDOSO et al, 2010;KELLY et al, 2013), a differential diagnosis based on identification of the etiological agents is important, in order to assess the zoonotic potential and the best therapy for the pathogens involved.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study conducted in four different regions of India by using PCR technique, it was reported that 21% of the enrolled dogs were having E. canis in their blood (Rani et al 2011). In a recent study conducted in St. Kitts (West Indies), the prevalence of E. canis in collected dog samples was found to be 27% using quantitative PCR (Kelly et al 2013). Rojas et al (2014) have also reported 34% prevalence of E. canis in dogs from Costa Rica (Rojas et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Infections of these pathogens range in their effects from asymptomatic to severe illness. The compatibility of clinical signs includes fever, anorexia, lymphadenomegaly, pale mucous membranes, lethargy, scleral injection, anemia, weight loss, icterus and thrombocytopenia [7][8][9].…”
Section: Introductionmentioning
confidence: 99%